Berbagai Faktor yang Berpengaruh Terhadap Kejadian Rawat Inap Jemaah Diabetes Melitus di Arab Saudi (Studi Kasus Kontrol di Embarkasi Adisumarmo) - Rakhamanto Wahyu Nugroho; Suharyo Hadisaputro; Widiastuti Samekto; Sugiri Sugiri; Djoko Trihadi Lukmono (Jurnal Epidemiologi Kesehatan Komunitas, 2017)
Background : Given the magnitude of high-risk DM throughout Hajj embarkation and pilgrims hospitalization in Saudi Arabia, we need for prevention and control of DM pilgrims hospitalization case in Saudi Arabia. To prevent and control the incidence of hospitalization, public and the government needs to know the various factors that influence the incidence of hospitalization.Methods : The study was observational with case control study design. The study population is the assembly of DM in Adisumarmo Hajj embarkation. Number of samples of 135 people with 45 cases and 90 controls. The dependent variable is inpatient diabetic in Saudi Arabia , the independent variable is demographics (age, gender, education level), comorbidities (hypertension, heart disease, dyslipidemia, stroke, obesity), behavior (compliance with diet and medication), the knowledge, long suffered diabetic, environment (temperature and duration in Saudi Arabia.Results : Most respondents had long suffered from diabetes. The level of compliance of respondents to the diet DM and DM medication adherence is good. Multivariate factors that influence the incidence of hospitalization DM pilgrims in Saudi Arabia is a dietary adherence (p=0.001, OR=14,95% CI= 2.78 to 70.97 ) and knowledge (p = 0.003, OR = 6.5; 95% CI=0.59 to 4.51).Conclusion : Factors that influence the incidence of DM pilgrims hospitalization in Saudi Arabia is a dietary adherence and knowledge.